Mobile Technology Application for Improved Urine Concentration Measurement Pilot Study - Walawender, Laura; Patterson, Jeremy; Strouse, Robert; Ketz, John; Saxena, Vijay; Alexy, Emily; Schwaderer, Andrew (Frontiers in Pediatrics, 2018)
Objectives: Low hydration has a deleterious effect on many conditions. In the absence of a urine concentrating defect, urine concentration is a marker of hydration status. However, markers to evaluate hydration status have not been well studied in children. The objectives of this paper are to compare measures of thirst and urine concentration in children and to develop a novel mobile technology application to measure urine concentration. Study Design: Children age 12-17 years were selected (n=21) for this pilot study. Thirst perception, specific gravity (automated dipstick analysis and refractometer), and urine color scale results were correlated to urine osmolality. The technology department developed a mobile technology camera application to measure light penetrance into urine which was tested on 25 random anonymized urine samples. Results: The patient’s thirst perception and color scale as well as two researchers color scale did not significantly correlate with osmolality. Correlation between osmolality and hydration markers resulted in the following Pearson coefficients: SG automated dipstick, 0.61 (P 0.003); SG refractometer, 0.98 (P < 0.0001); urine color scale (patient), 0.37 (P 0.10), and light penetrance, -0.77 (P < 0.0001). The correlation of light penetrance with osmolality was stronger than all measures except SG by refractometer and osmolality. Conclusion: The mobile technology application may be a more accurate tool for urine concentration measurement than specific gravity by automated dipstick, subjective thirst, and urine color scale, but lags behind specific gravity measured by refractometer. The mobile technology application is a step towards patient oriented hydration strategies.